Assessing policy coherence in EU marine governance: A legal and institutional methodological framework - Froukje Maria Platjouw; Gunnar Sander; Laura Friedrich; Saskia Trubbach; Suvi-Tuuli Puharinen; Cristian Passarello; Niko Soininen; Jonas Kyrönviita; Ben Boteler (Marine Policy, 2026)

Towards a strategy for offshore installations to enhance the environmental status of coastal seas: Multi-use concepts for ecosystem restoration - Sabine Horn; Bela H. Buck; Rudolf Amann; Ben Boteler; Kira Gee; Nils Goseberg; Maurits Halbach; Anneke Heins; Katja Heubel; Andreas Kannen; Dietmar Kraft; Carsten Lemmen; et al. (Marine Policy, 2025)

Setting the course: aligning European Union marine pollution policy ambitions with environmental realities - Lisa I. Devriese; Thomas J. Verleye; Thomais Vlachogianni; Thomas Maes; Ben Boteler; Linda Del Savio; Andy M. Booth; Kathrin Kopke (Frontiers in Marine Science, 2025)
Pollution in coastal and marine waters is a global challenge that transcends national boundaries, affecting interconnected seas, the ocean and broader ecosystems. Addressing marine pollution requires policies that encompass not only the marine domain but the entire ecosystem, including human societies. Therefore, a comprehensive and integrated governance approach, linking land-based sources to marine environments, is essential for effective pollution management and mitigation. This study assesses the current environmental status of persistent, long-lasting and emerging pollutants (PCBs, excess nutrients, microplastics, PFAS, and underwater noise) and cumulative effects of pollution, and compares these with the set European Union (EU) environmental goals and ambitions. A systematic review of EU policy documents reveals that several targets are unclear, arbitrary, and often unattainable, limiting the effectiveness of current strategies. This paper presents five actionable recommendations to strengthen marine environmental policy, emphasizing the need for better alignment between EU ambitions and environmental realities. To enhance EU pollution policies, it is crucial to reinforce regulatory frameworks, ensure the effective enforcement of existing legislation, foster collaboration across sectors, and empower citizens and NGOs. Additionally, integrating health and pollution policies, ensuring public access to pollution data and knowledge, and establishing international leadership in pollution efforts are key for making informed decisions and achieving ambitious pollution reduction targets.

Borderless conservation: Integrating connectivity into high seas conservation efforts for the Salas y Gómez and Nazca ridges - Ben Boteler; Daniel Wagner; Carole Durussel; Emily Stokes; Carlos F. Gaymer; Alan M. Friedlander; Daniel C. Dunn; Felipe Paredes Vargas; David Veliz; Carolina Hazin (Frontiers in Marine Science, 2022)
Connectivity is essential to consider in area-based marine conservation measures because it greatly impacts vital ecological processes (e.g., recycling nutrients, regulating temperature, sequestering carbon, and supporting the life cycle of species). However, it is generally not well studied or integrated into conservation measures, particularly in the Southeast Pacific. This region is home to the Salas y Gómez and Nazca ridges, two adjacent seamount chains that stretch between the Peruvian coast and Rapa Nui (i.e., Easter Island). The area has been recognized for its exceptional natural and cultural significance as well as one of the most important global areas to protect. However, over 73% of the ridges are in areas beyond national jurisdiction, where they are unprotected and under threat. This study provides a synthesis of what we know about connectivity in the Salas y Gómez and Nazca ridges and provides practical recommendations for integrating this knowledge into conservation and management measures for the region. While data on connectivity is still limited, it should not constrain the development of conservation measures, which should be co-designed and co-developed, leveraging the expertise of international working groups throughout the region. Due to their high rates of endemism, as well as importance as migratory corridors, enacting large-scale conservation measures would address important conservation considerations for both connectivity and endemism. Enacting such large-scale conservation measures would not only elevate the Salas y Gómez and Nazca ridges as an exemplary case study, providing lessons for other marine regions seeking to implement similar measures, but could also help raise awareness on the severity of externally originating threats like climate change and plastic pollution to global audiences.